Developing Indonesian Perspectives in International Relations: The Argument For “Depok School” - Fitriani, Evi (Global: Jurnal Politik Internasional, 2022)
This article lies arguments to build a “Depok School” in International Relations. The gap between developed and developing countries is visible in practice and the paradigm for understanding the phenomenon of international relations dominated by the perspective of major (Western) countries. Through an analysis of empirical and theoretical developments in the study of International Relations, this paper examines the need for non-Western perspectives.. The mandate from the Preamble to the 1945 Constitution of the Republic of Indonesia provides the axiological basis for a more suitable analytical framework that can capture the unique phenomena of Indonesia and developing countries, which is rarely caught by Western lenses. To build the “Depok School”, the 5G and 3D ideas put forward by Juwono Sudarsono are an important starting point. Juwono’s perspective emphasis linkages between five geographical scopes (local, provincial, national, regional, and global) and three dimensions of issues (political-security, economy, and social-culture) in analyzing international and global phenomena.